Information and learning in oligopoly: An experiment - Maria Bigoni; Margherita Fort (Institute for the Study of Labor (IZA), 2013)
This paper presents an experiment on learning in repeated games, which complements the analysis of players' actual choices with data on the information acquisition process they follow. Subjects play a repeated Cournot oligopoly, with limited a priori information. The econometrics hinges on a model built upon Experience Weighted Attraction learning, and the simultaneous analysis of data on the information gathered and on actions taken by the subjects. Results suggest that learning is a composite process, in which different components coexist. Adaptive learning emerges as the leading element, but when subjects look at the strategies individually adopted by their competitors they tend to imitate the most successful behavior, which makes markets more competitive. Reinforcement learning also plays a role, as subjects favor strategies that have yielded higher profits in the past.
Keywords: L13; C92; C72; 330; information; imitation; Cournot oligopoly; EWA learning; Oligopol; Imitationswettbewerb; Lernprozess; Wiederholte Spiele; Test